The Rights of Immigrant Workers in the European Union : an Evaluation of the EU Public Policy Process and the Legal Status of Labour Immigrants from the Maghreb Countries in the New Receiving States. (BRILL, 2002)
This title evaluates the evolving policies towards third country nationals residing and working in the European Union (EU). Other studies have analysed the existing legal framework of citizenship and migrants' rights in the EU and the flow of migrants into the community. However, much less comparative research has been carried out about the actual position and the practice of migrants' rights in the receiving countries, in the context of an ever integrating EU and the removal of internal borders. The focus of this book is on the consequences of the increasing number of Maghrebin workers residing in Italy and Spain - both for EU policy and with respect to these two countries as relatively young receiving states.